The plant vampire diaries: a historic perspective on Cuscuta research - Hartenstein, Maleen; Albert, Markus; Krause, Kirsten (Journal of Experimental Botany, 2023)
The angiosperm genus Cuscuta lives as an almost achlorophyllous root- and leafless holoparasite and has therefore occupied scientists for more than a century. The 'evolution' of Cuscuta research started with early studies that established the phylogenetic framework for this unusual genus. It continued to produce groundbreaking cytological, morphological, and physiological insight throughout the second half of the 20th century and culminated in the last two decades in exciting discoveries regarding the molecular basis of Cuscuta parasitism that were facilitated by the modern 'omics' tools and traceable fluorescent marker technologies of the 21st century. This review will show how present activities are inspired by those past breakthroughs. It will describe significant milestones and recurring themes of Cuscuta research and connect these to the remaining as well as newly evolving questions and future directions in this research field that is expected to sustain its strong growth in the future.
CRIS-Team WoS Importer:2023-04-07